Mulching as best management practice to reduce surface runoff and erosion in steep clayey olive groves - Giuseppe Bombino; Pietro Denisi; José Alfonso Gómez; Demetrio Antonio Zema (International Soil and Water Conservation Research, 2021)
No-tillage and soil mulching with pruning residues, applied in olive groves of the semi-arid Mediterranean environment, as erosion control practices still practice not fully studied. This study has evaluated the saturated hydraulic conductivity (Ksat), surface runoff (SR) and soil erosion (SL) under rainfall at plot scale throughout two years in four different management practices, total soil cover with a net (SP), mechanical tillage (MT) and mulching by vegetal residues at 3,5·103 and 17,5·103 kg ha−1 of dry matter (NTR350 and NTR1750), in an olive grove of Southern Italy. Ksat varied between 1.6 (MT) and 25.1 (NTR1750) mm/h. A clear reduction in runoff and soil losses was detected for the mulch-based practices when compared to MT, from 20 to 32% in the runoff coefficient and 75–80% in SL, with higher reductions in the NTR1750. This reduction in SL can be mainly explained by the reduction in SR and rain-splash, interrill and rill erosion, due to protection by mulch residues, which increased the vegetal cover and organic matter content of mulched plots. The vegetal cover was on average higher in SP (33%), NTR1750 (25%) and NTR350 (22%), and lower in MT (12%). The mean organic matter content of soil was 2.01%, 1.69%,1.34% and 0.82% for NTR1750, NTR350, SP and MT respectively.Overall, the results quantify the impact of soil mulching with pruning residues at different doses, which will provide guidelines to control and mitigate the hydrological response of clayey and steep soils in Mediterranean olive groves, analysing the associated environmental and economic benefits.